ADMINISTRATIVE WORK: GENESIS OF IDEAS AND PROSPECTS IN INNOVATION ECONOMICS - Anna P. Bagirova; Asya S. Vavilova (Advanced Engineering Research, 2011)
The analysis results of the development of ideas related to understanding the essence of work as a whole, and administrative work in particular, are presented. Comparative analysis of management and administrative work is done. Correlation ambiguousness of these categories is specified. The trends influencing the transformation of administrative work and new mechanisms of its implementation under the transition to innovation economy are described.